Perioperative immunonutrition intervention on postoperative outcomes among gynaecological cancer patients under enhanced recovery after surgery setting - Ho, Chiou Yi; Daud, Zulfitri Azuan Mat; Mohd Yusof, Barakatun Nisak; Abdul Majid, Hazreen; Omar, Jamil; Mohd Abas, Mohd Norazam; Md Hanapiah, Suhaila (Springer Science and Business Media Deutschland GmbH, 2026)
Purpose: Enhanced Recovery After Surgery (ERAS) and immunonutrition (IMN) are established strategies for enhancing postoperative outcomes and modulating immune response. However, current research often overlooks the influence of patients’ nutritional status and acceptability in the effectiveness of these combined therapies. The study was aimed at evaluating the effectiveness of perioperative IMN in gynaecological cancer (GC) patients. Method: This was an open-label randomised controlled trial. The primary outcomes were postoperative hospitalisation, nutritional status, and functional status. Results: A total of 110 participants were randomised into the perioperative IMN intervention (I-ERAS) or control (CO) group under an ERAS protocol. Mean age was 50.15 ± 13.07 years in I-ERAS and 49.27 ± 13.80 years in CO. Compared with CO, I-ERAS had a significantly shorter hospital stay (81.5 ± 40.9 h vs. 102.7 ± 58.7 h, p < 0.05) and faster gastrointestinal recovery, including earlier transition to a solid diet and return of bowel sounds. Importantly, none of the I-ERAS patients were readmitted within 30 days, compared with a 7.4% readmission rate in the CO group (p < 0.05). In addition, I-ERAS patients had improved wound healing (p < 0.05); better preservation of nutritional status (p < 0.05), a more favourable inflammatory profile (p < 0.01), and faster recovery of functional status (p < 0.05) and physical performance (p < 0.01). Conclusion: Perioperative IMN within an ERAS protocol for GC surgery is a valuable intervention that reduces hospitalisation, enhances wound healing, improves inflammatory profiles, and lowers readmissions, making it suitable for routine ERAS practice. Trial registration: NCT06039306, dated 14 September 2024 Protocol version: POIMNERAS2023, version 2, September 2023